2023
DOI: 10.3389/fonc.2023.1084523
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning-based neddylation landscape indicates different prognosis and immune microenvironment in endometrial cancer

Abstract: Endometrial cancer (EC) is women’s fourth most common malignant tumor. Neddylation plays a significant role in many diseases; however, the effect of neddylation and neddylation-related genes (NRGs) on EC is rarely reported. In this study, we first used MLN4924 to affect the activation of neddylation in different cell lines (Ishikawa and HEC-1-A) and determined the critical role of neddylation-related pathways for EC progression. Subsequently, we screened 17 prognostic NRGs based on expression files of the TCGA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…To estimate immune cell abundance in different samples, we employed a range of methods including ssGSEA, TIMER, CIBERSORT, QUANTISEQ, MCP‐counter, XCELL, and EPIC. Moreover, the ESTIMATE algorithm was utilized to calculate the immune score and stromal score, serving as indicators of the overall microenvironmental status 29 . Moreover, we downloaded the IMvigor‐210 cohort from existing reference which had undergone immune checkpoint treatment to generate risk scores.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…To estimate immune cell abundance in different samples, we employed a range of methods including ssGSEA, TIMER, CIBERSORT, QUANTISEQ, MCP‐counter, XCELL, and EPIC. Moreover, the ESTIMATE algorithm was utilized to calculate the immune score and stromal score, serving as indicators of the overall microenvironmental status 29 . Moreover, we downloaded the IMvigor‐210 cohort from existing reference which had undergone immune checkpoint treatment to generate risk scores.…”
Section: Methodsmentioning
confidence: 99%
“…Each dataset was normalized separately, with the gene mean/SD being normalized to 1. Variable screening, which required a minimum threshold of four variables, was performed using Lasso, CoxBoost, random survival forest (RSF), StepCox [both], and StepCox [backward] in the TCGA‐OV cohort 29 . Subsequently, a combination of 10 machine learning algorithms (lasso, RSF, GBM, Survival‐SVM, SuperPC, ridge regression, plsRcox, CoxBoost, StepCox, and enet) were used to create a composite model, with RSF being identified as the best prognostic model, based on the average C‐index within all cohorts.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…These approaches can enable the identification of specific molecular features associated with pathway activation and disease progression, as well as the development of predictive models for individual patient response to targeted therapies. 5 For instance, a recent study demonstrated the utility of machine learning in identifying gene expression patterns associated with PI3K/AKT/mTOR status in uveal melanoma, 6 highlighting the potential of these methods for identifying biomarkers of treatment response in PDAC as well. Moreover, the integration of machine learning with other high-throughput omics data, 7,8 such as proteomics and metabolomics, may provide a more comprehensive understanding of the molecular mechanisms underlying PDAC and the role of the PI3K/AKT/mTOR pathway in this disease.…”
mentioning
confidence: 99%